1999
DOI: 10.1046/j.1432-1327.1999.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Subunit dissociation and inactivation of pyruvate kinase by hydrostatic pressure

Abstract: The effect of hydrostatic pressure on the stability of tetrameric rabbit muscle pyruvate kinase was investigated by enzyme activity measurements, size-exclusion chromatography, circular dichroism and fluorescence spectroscopies. Under nonreducing conditions, enzyme activity was irreversibly inhibited by increasing pressure and was completely abolished at 350 MPa. Inhibition was dependent on the concentration of pyruvate kinase, indicating that it was related to pressure-induced subunit dissociation. Size-exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, the increase of b2 band seems to be due to a pressure-induced dissociation of tetramer pyruvate kinase, composed by 58 KDa pyruvate kinase monomers. In agreement with this, a previous investigation showed that HHP treatment causes dissociation and inactivation of pyruvate kinase (De Felice et al 1999). This effect of the HHP strength on sarcoplasmic proteins was not altered after a 3-month storage at -10 ºC.…”
Section: Sds-page Profile Analysis and Ms-ms Identificationsupporting
confidence: 87%
“…However, the increase of b2 band seems to be due to a pressure-induced dissociation of tetramer pyruvate kinase, composed by 58 KDa pyruvate kinase monomers. In agreement with this, a previous investigation showed that HHP treatment causes dissociation and inactivation of pyruvate kinase (De Felice et al 1999). This effect of the HHP strength on sarcoplasmic proteins was not altered after a 3-month storage at -10 ºC.…”
Section: Sds-page Profile Analysis and Ms-ms Identificationsupporting
confidence: 87%
“…The observation of the stable dimer is relevant to our current consideration [171][172][173][174], given the focus on the tetramer to dimer transition in studies of M 2 PYK in cancer. However, indications that the dimeric form of M 1 PYK is active are thought to be artifacts because PEP stabilizes the tetrameric form of that enzyme [173,175,176]. Therefore, even when isolated dimers of the M 1 PYK protein are added to an assay, the presence of PEP in the assay causes dimers to rapid assemble into active tetramers.…”
Section: Pyk Tetramer-dimer Equilibrium May Not Have Physiological Relevancementioning
confidence: 99%
“…Pyruvate kinase has previously been found to be a pressure-sensitive enzyme and to undergo adaptational changes in deep-sea animals (26,57). The requirement for this isozyme could have been a reflection of the medium conditions employed (growth under glucosefermenting conditions).…”
Section: (I) Previously Isolated Genes (Classes T and I) (Strains Fl4mentioning
confidence: 99%